Factors affecting the effectiveness of accounting information systems in the Vietnamese small and medium enterprises - Do Huyen Trang; Le Mong Huyen; Le Thy Ha Van (My University, 1974)
Factors affecting the effectiveness of accounting information systems in the Vietnamese small and medium enterprises
Keywords: Accounting information systems; Effectiveness; SME